Bio artificial pancreas – the immune barrier and oxygen deficiency. (March 2014) - Barkai, Uriel; Ludwig, Barbara; Bornstein, Stefan R.; Zimermann, Baruch; Gendler, Zohar; Rotem, Avi
<x xml:space="preserve">Abstract</x> Background Xenogeneic transplantation of islets of Langerhans into type I diabetes patients imposes a major challenge. This is even more exaggerated when the target is set as xenotransplantation of islets in relatively oxygen poor environment without the use of immunosuppressive therapy. To overcome these hurdles, adequate encapsulation technique and active oxygen supply should be employed. Methods A two‐article device was developed (the βAir). The first contains an implantable bioreactor module comprising of islets of Langerhans encapsulated in alginate hydrogel and protected from the host immune system by a complex membrane. The second is an external oxygen injection device for replenishing of the islet biomass in the implantable device once a day. Results Both small and large diabetic animal models (rats and pigs) were experimented. The βAir device proved: (i) ability to maintain near normal glycemic control in rats transplanted with either isogeneic or allogeneic islets for a period of over 6 months and in pigs transplanted with rat islets using marginal dose of islets (~6, 500 IEQ/kg) for a period of up to 75 days; (ii) ability to maintain adequate oxygen tension required to nourish the islets graft for a period of 24 h while maintaining optimal islet's function. (iii) long term separation of transplanted graft from host immune system thus maintaining normal islets function in rat allotype, in rat‐to‐pig and in human‐to‐rat transplantation systems and (iv) high level of biocompatibility and tolerability of the device. Conclusion The βAir device proved to offer functional solution to islets transplantation in allogeneic and xenogeneic setting. It may provide a solution to transplantation of porcine islets to diabetic patients. References [1] Barkai U, Weir GC, Colton CK et al. Enhanced oxygen supply improves islet viability in a new bioartificial pancreas. Cell Transplant. 2013; 22: 1463–1476. [2] Neufeld T, Ludwig B, Barkai U et al. The efficacy of an immunoisolating membrane system for islet xenotransplantation in minipigs. PLoS One. 2013; 8(8): e70150.